Grupo mediano de personas.
De izquierda a derecha Rafael Ángel Rodríguez Fallas, Álvaro Avilés Mata, Juan Humberto Cevo Guzmán, Chester Zelaya Goodman, Sergio Flores Álvarez, Orlando Saborío Elizondo, Carlos Luis Fallas Monge, Ceferino Rodríguez Zúñiga, Héctor E. Mejía Ávila